PENERAPAN ARSITEKTUR METAFORA PADA PERANCANGAN STADION AKUATIK DI KABUPATEN SLEMAN D.I. YOGYAKARTA - Dopi Rahmawati; Harfa Iskandaria; Anggraeni Dyah Sulistiowati (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2023)
Water sports are one of the sports that have many types in the competition. Every year in Indonesia, there are always water sports competitions such as water polo, track swimming, beautiful swimming and beautiful jumping. Water sports are quite attractive to some people from young to Old. In the implementation of water sports requires facilities that can accommodate these activities. The facility is called a sports arena or internationally known as an Aquatic Stadium. The number of water sports competitions in Sleman Regency makes several competition events held in separate places such as FIK UNY and Depok Sports Centre. Aquatic Stadium in Sleman Regency is a place to meet the needs in aquatic sports that use international standards. This aquatic stadium has a function as a sports facility intended for athletes, especially domicile D.I. Yogyakarta and as a means of recreation for the community among young and old. Aquatic Stadium is expected to be a new place for athletes and the public who want to do water sports activities with complete facilities of international standard. An architectural metaphor will be applied to the concept of building an aquatic stadium which describes the characteristics of the building’s funciton as a water sports building.